Optimalisasi Nilai Perusahaan Melalui Moderasi Peran Good Corporate Governance - Nur Ravita Hanun; Aisha Hanif; Surya Ningrum (Jurnal Reviu Akuntansi dan Keuangan, 2023)
Purpose: This study aims to determine the role of GCG in moderating the effect of CSR Disclosure, Profitability and Intellectual Capital on Company Value. Methodology/approach: The number of samples in this study was 87 samples determined by the purposive sampling method. Data analysis techniques using Partial Least Square (PLS) software. Findings: The results showed that Intelectual Capital has no effect on company value, while CSR disclosure and profitability affect company value. In addition, the results of moderation tests show that GCG cannot moderate the effect of CSR disclosure, profitability and IC on company value. Practical implications: The basic chemical industry carries out social responsibility to the community by expressing Corporate Social Responsibility. Stakeholders tend to appreciate companies that pay more attention to social responsibility so as to produce a good image and increase profitability. Originality/value: The novelty of this research is about the object of research in basic industry and chemistry. It also adds the Intelectual Capital variable as an independent variable.